2009
DOI: 10.1079/pavsnnr20094007
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, biology and integrated management of the pea leaf weevil, Sitona lineatus L. (Coleoptera: Curculionidae), with an analysis of research needs.

Abstract: The pea leaf weevil, Sitona lineatus L. (Coleoptera, Curculionidae), is a significant pest of field pea (Pisum sativum L.) and broad bean (Vicia faba L.) crops throughout Europe, Asia, Africa and North America and it has recently become an established pest in the Canadian prairies. The geographical expansion and current distribution of S. lineatus, its life history, economic impact and control strategies are reviewed. Primary hosts of the pea leaf weevil, on which pre-imaginal development can occur, are identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 0 publications
1
47
0
5
Order By: Relevance
“…Sitona lineatus was discovered in southern Alberta in 1997 (Vankosky et al 2009), but its distribution and damage in western Canada have not been reported previously. Populations of S. lineatus increased dramatically in southern Alberta from 2005 to 2007 as indicated by the frequency of feeding notches in P. sativum seedlings; however, the outbreak of 2007 was followed in 2008 by a drastic decline in damage (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Sitona lineatus was discovered in southern Alberta in 1997 (Vankosky et al 2009), but its distribution and damage in western Canada have not been reported previously. Populations of S. lineatus increased dramatically in southern Alberta from 2005 to 2007 as indicated by the frequency of feeding notches in P. sativum seedlings; however, the outbreak of 2007 was followed in 2008 by a drastic decline in damage (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…This group of species includes P. cruciferae (Westdal and Romanow 1972), P. striolata (Bain and LeSage 1998), D. radicum (Gibson and Treherne 1917), C. nasturtii (Canadian Food Inspection Agency 2009), and S. mosellana (Felt 1912). A second invasion pathway, apparently taken by C. obstrictus (Baker 1936;Cárcamo et al 2001) and S. lineatus (Vankosky et al 2009), involved their introduction to western North America with subsequent dispersal south to the Pacific Northwest followed by eastward movement to the Northern Great Plains. A third group of species, comprising P. xylostella Hopkinson andSoroka 2010), A. pisum (McVicar et al 2009), and probably S. avenae, do not generally overwinter well in western Canada but are carried northward in spring on strong air flow from southern regions of the USA or from Mexico.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations